2014
DOI: 10.1371/journal.pone.0084616
|View full text |Cite
|
Sign up to set email alerts
|

Specific Relationship between Excitatory Inputs and Climbing Fiber Receptive Fields in Deep Cerebellar Nuclear Neurons

Abstract: Many mossy fiber pathways to the neurons of the deep cerebellar nucleus (DCN) originate from the spinal motor circuitry. For cutaneously activated spinal neurons, the receptive field is a tag indicating the specific motor function the spinal neuron has. Similarly, the climbing fiber receptive field of the DCN neuron reflects the specific motor output function of the DCN neuron. To explore the relationship between the motor information the DCN neuron receives and the output it issues, we made patch clamp record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…The IO was stimulated once, and a skin burst stimulation of 50 pulses at 333 Hz was started 10 ms in advance in order for the first mf input to arrive at the same time as the cf input (the mf input evoked from the periphery needs at in the order of 10 ms to reach the cerebellar nuclei [3]).…”
Section: Methodsmentioning
confidence: 99%
“…The IO was stimulated once, and a skin burst stimulation of 50 pulses at 333 Hz was started 10 ms in advance in order for the first mf input to arrive at the same time as the cf input (the mf input evoked from the periphery needs at in the order of 10 ms to reach the cerebellar nuclei [3]).…”
Section: Methodsmentioning
confidence: 99%
“…Spinal interneurons are involved in the muscle synergy selection when the spinal motor circuitry is driven by descending motor control signals from the neocortex and/or subcortical motor systems [88]. Hence, the cerebellum can use the spinocerebellar systems to be informed about the relative excitatory drive on specific synergical components and on the low level motor functions resident in the spinal cord [89, 90]. …”
Section: Spinocerebellar Circuitry—consequences For the Organization mentioning
confidence: 99%
“…An array of Purkinje cells that compose a functional microzone, and which targets the same group of cells in the efferent cerebellar nucleus and therefore can be considered a “super”-Purkinje cell, has a tremendous associative power [91]. One important possible consequence of this arrangement is that the cerebellum can associate many specific basal (spinal) synergy components in the right temporal order to help synthesize compound movements [89]. Although there is a debate on the pattern of convergence of mossy fiber information in individual granule cells, at least for limb controlling areas of the cerebellar cortex mossy fiber information from individual functional pathways is directly transmitted through granule cells and reflected in the output of the Purkinje cells [92, 93].…”
Section: Spinocerebellar Circuitry—consequences For the Organization mentioning
confidence: 99%
“…We recently studied the effect of direct and indirect MF and CF inputs to the CN cells in in vivo whole cell recordings from the anterior interposed nucleus [33, 112]. We found that the spontaneous synaptic activity of the CN cells primarily consisted of two alternating patterns.…”
Section: Generation Of Motor Regulatory Signals In Cn Neuronsmentioning
confidence: 99%
“…Electrical as well as manual stimulation of the cutaneous MF receptive fields of the CN neurons [112] generated substantial excitatory modulations of their membrane potential. Based on the latency times of these responses and the fact that electrical stimulation of a known source of MF-CN synapses evoked monosynaptic EPSPs in these neurons, the responses could be ascribed to the direct excitatory synapses formed by MF collaterals [112]. This input modulated the CN cell activity in an apparently linear fashion and the firing rate modulations were of similar magnitudes as those observed during behavioral recordings of interpositus neurons [113].…”
Section: Generation Of Motor Regulatory Signals In Cn Neuronsmentioning
confidence: 99%